Citizens' perspectives on relocating care: a scoping review - L. J. Damen; L. H. D. Van Tuyl; J. C. Korevaar; B. J. Knottnerus; J. D. De Jong (BMC, 2024)
Abstract Background Healthcare systems around the world are facing large challenges. There are increasing demands and costs while at the same time a diminishing health workforce. Without reform, healthcare systems are unsustainable. Relocating care, for example, from hospitals to sites closer to patients' homes, is expected to make a key contribution to keeping healthcare sustainable. Given the significant impact of this initiative on citizens, we conducted a scoping review to provide insight into the factors that influence citizens' attitudes towards relocating care. Method A scoping review was conducted. The search was performed in the following databases: Pubmed, Embase, Cinahl, and Scopus. Articles had to include relocating healthcare and citizens' perspectives on this topic and the articles had to be about a European country with a strong primary care system. After applying the inclusion and exclusion criteria, 70 articles remained. Results Factors positively influencing citizens' attitudes towards relocating care included: convenience, familiarity, accessibility, patients having more control over their disease, and privacy. Factors influencing negative attitudes included: concerns about the quality of care, familiarity, the lack of physical examination, contact with others, convenience, and privacy. Furthermore, in general, most citizens preferred to relocate care in the studies we found, especially from the hospital to care provided at home. Conclusion Several factors influencing the attitude of citizens towards relocating care were found. These factors are very important when determining citizens' preferences for the location of their healthcare. The majority of studies in this review reported that citizens are in favour of relocating care. In general citizens' perspectives on relocating care are very often missing in articles. It was significant that very few studies on relocation from the hospital to the general practitioner were identified.